Laser annealing-induced phase transformation behaviors of high entropy metal alloy, oxide, and nitride nanoparticle combinations - Li, Yun (2023)
High entropy materials made up of dissimilar elements have enormous potentials in various fields and applications such as catalysis, energy generation and bioengineering. Developments of facile rapid synthesis routes toward functional multicomponent nanoparticles (NPs) of metals and ceramics with control of single/mixed crystalline structure configurations as well as understanding their transformative behaviors to enable unexpected properties, however, has remained challenging. Here a transient laser heating strategy to generate high entropy metal alloy, oxide, and nitride nanoparticles (HE-A/O/N NPs) is described. Laser irradiation of the identical metal salt mixture under different millisecond heating times provides direct control of cooling rates and thereby results in HEA NPs with tunable single- and multiphasic solid solution characteristics, atomic compositions, nanoparticle morphologies, and physicochemical properties. Extending the elemental selection to nitride-forming precursors enables laser-induced carbothermal reduction and nitridation of high entropy tetragonal rutile oxide nanoparticlesNPs to the cubic rock salt nitride phase. The combination of laser heating with spatially resolved X-ray diffraction facilitates combinatorial studies of phase transitions and reaction pathways of multicomponent nanoparticles. These findings provide a general strategy to design nonequilibrium multicomponent metal alloys and ceramic materials amalgamations for fundamental studies and practical applications such as carbon nanotube growth, water splitting, and antimicrobial applications.